A green approach for the synthesis of 2-oxo-1,2,3,4-tetrahydropyrimidines through oxidative functionalization of methyl arenes/benzyl derivatives via in situ generated urea - Singh V.; Rajput K.; Verma P.; Singh S.; Srivastava V. (My University, 2025)
The present work revealed a novel one-pot synthesis of 2-oxo-1,2,3,4-tetrahydropyrimidines. It involved the use of methyl arenes as a surrogate of aldehydes, in situ generation of urea, and eco-friendly lactic acid as a green catalyst for the synthesis of the desired product in solvent-free conditions via the Biginelli reaction. The appealing characteristics of the proposed protocol include; environmentally benign mild reaction conditions, readily available and cost-effective chemicals as starting material, invaluable bio-based green catalyst, aerobic conditions, shorter reaction time, tolerance to distinct functional groups, and easy isolation of final product with high yield value even without the use of chromatographic separation technique. Graphical abstract: [Figure not available: see fulltext.] © 2023, The Author(s), under exclusive licence to Springer Nature B.V.